Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Quang Trung

Giải pt: \(\sqrt{3x^2-7x+3}-\sqrt{x^2-2}=\sqrt{3x^2-5x-1}-\sqrt{x^2-3x+4}\)

Thắng Nguyễn
4 tháng 2 2016 lúc 22:12

\(\Leftrightarrow\sqrt{12-7x}-\sqrt{x^2-x}=\sqrt{3x^2-5x-1}-\sqrt{x^2-3x+4}\)

\(\Rightarrow-\sqrt{3x^2-5x-1}-\sqrt{x^2-x}+\sqrt{x^2-3x+4}+\sqrt{12-7x}=0\)

=>\(x\approx-3,4579061804411\)

Thắng Nguyễn
3 tháng 2 2016 lúc 20:55

ra số rất lẻ

Nguyễn Quang Trung
4 tháng 2 2016 lúc 22:28

bấm máy nữa chứ gì =.=


Các câu hỏi tương tự
Ngô quang minh
Xem chi tiết
Võ Hồng Phúc
Xem chi tiết
Nguyễn An
Xem chi tiết
nguyenhoangtung
Xem chi tiết
Trần Văn Quyết
Xem chi tiết
Phác Tú Anh
Xem chi tiết
vodiem
Xem chi tiết
nguyễn thị anh thơ
Xem chi tiết
hoanghongnhung
Xem chi tiết